Digital Marketing : The Solution of Omah Japo to Survive in Pandemic Covid-19 - Muhammad Fadeli (Universitas Merdeka Malang, 2022)
The pandemic resulted in a decline in MSME turnover by up to 75%, dueto government restrictions through PSBB and PPKM. Through digital marketing, business actors can promote their products, interact with users, and even transact directly. The challenge for MSMEs is a digital marketing strategy; create image content, create video content, and advertise such content through social media. The purpose of the study was to determine the role of digital marketing in maintaining a business. The research approach is a qualitative descriptive naturalistic involving the most of business informants Omah Japo. Data collection techniques were carried out through observation and interviews. The results showed that Omah Japo's digital marketing was social media Facebook, Instagram, and WhatsApp groups. Through these three media, it is an oven that Omah Japo is able to maintain consumer interest with stable sales figures.Keywords: Digital Marketing, Covid-19, Omah Japo